Mechanical, microstructural and in-situ neutron diffraction investigations of equi-biaxial Bauschinger effects in an interstitial-free DC06 steel - Härtel, Markus; Illgen, Christian; Panzner, Tobias; Bruder, Enrico; Schmaltz, Stefan; Van Petegem, Steven; Willner, Kai; Durst, Karsten; Van Swygenhoven, Helena; Wagner, Martin F.X. (International Journal of Plasticity, 2022)
Bauschinger effects typically describe a reduction of yield strength after a load path change under uniaxial loading conditions. Here, we use in-plane loading to investigate, for the first time, Bauschinger effects in the sheet metal DC06 under well-defined equi-biaxial loading conditions: We first performed equi-biaxial tensile tests with cruciform specimens up to different maximum tensile strains. Then, smaller specimens were prepared from the equi-biaxially deformed inner part of the cruciform specimens and subjected to equi-biaxial compression. The mechanical results show that the material exhibits distinct Bauschinger effects when subjected to equi-biaxial load path changes, which differ from similar observations under uniaxial loading. Specifically, biaxial Bauschinger effect factors quickly reach a level of saturation, whereas the uniaxial Bauschinger effect factors keep decreasing. These Bauschinger effects can be rationalized by considering the results of TEM and EBSD investigations at the different stages of biaxial loading, particularly by considering the evolution of dislocation densities and the formation of substructures, which are related to intergranular and intragranular stresses. Furthermore, residual stress measurements by XRD and in-situ neutron diffraction show an increase of compressive residual stresses after equi-biaxial tensile deformation and unloading. These residual stresses facilitate yielding during subsequent equi-biaxial compression and therefore also clearly contribute to the observed Bauschinger effects.
CRIS-Team Scopus Importer:2022-12-23